The Development of Qur’anic Reading Methods in Postcolonial Indonesia: From Pesantren Traditions to Modern Methods - Sofian Effendi; M. Yusuf Fadlulloh (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
This article examines the historical development and contemporary transformation of Qur’anic reading methods in Indonesia, focusing on the shift from traditional pesantren-based transmission to diversified and institutionalized pedagogical systems. Drawing on a qualitative design that combines a systematic literature review and document analysis, this study analyzes 86 primary and secondary sources selected through the PRISMA framework. The analysis traces major phases of pedagogical change, from oral-based methods such as Baghdadiyah and Yasiniyah to modern approaches including Qiraati, Iqra’, Yanbu’a, An-Nahdliyah, and Tartil. The findings reveal that Qur’anic pedagogy in Indonesia has evolved through processes of systematization, standardization, and mass dissemination while maintaining continuity with classical tajwid and sanad traditions. This development reflects broader postcolonial dynamics marked by nation-building, educational modernization, and intensified engagement with global Islamic networks. The study further shows that the emergence of at least 271 methods by 2022 illustrates sustained pedagogical creativity and pluralization of religious authority. Overall, the evolution of Qur’anic reading methods represents a dynamic dialectic between preservation of religious authenticity and adaptation to contemporary educational demands, reshaping patterns of literacy, authority, and piety in Indonesian Muslim society.